Training or Battling a Monster of a Location-Based Augmented-Reality Game While Descending Stairs: An Observational Study of Inattentional Blindness and Deafness and Risk-Taking Inclinations - Ma, Hon-Ping; Chen, Ping-Ling; Linkov, Václav; Pai, Chih-Wei (Frontiers in Psychology, 2019)
Several emerging smartphone augmented-reality games such as “The Walking Dead: Our World”, “Jurassic World Alive”, and “Pokémon Go” require three primary tasks: training or battling a monster, capturing a monster, and searching for a monster, which involve different levels of perceptual load. Using Pokémon Go as a single case study, this study examined inattentional blindness and deafness and risk-taking inclinations among participants concurrently descending stairs and engaging in these three tasks. Participants descending stairs in Taipei Medical University were observed through recordings obtained from Wi-Fi cameras to determine whether they engaged in risk-taking behaviours such as hopping, not using the handrail, and stopping suddenly. After the participants descended the stairs, they were interviewed to obtain additional information regarding demographics, Pokémon tasks (training or battling a Pokémon, capturing a Pokémon, or searching for a Pokémon), data plan, and screen size. Inattentional blindness and deafness were investigated by determining whether participants saw something unusual, a police ascending the stairs, and heard the national anthem played by the police, respectively. In total, 1036 participants descended the stairs and underwent the interview between August 2016 and July 2018. Logistic regression models revealed that training or battling a Pokémon was most associated with inattentional blindness, deafness, not using the handrail, and stopping suddenly, whereas hopping behaviour was the commonest among those capturing a Pokémon. Other contributory factors include a large smartphone screen (≥5 in), unlimited mobile data, being an undergraduate student, and an increase in the daily gaming hours. Development of smartphone apps towards detection of stair locomotion may be beneficial for curbing phone use in general and AR game playing in particular.